An adaptive power control mechanism in femtocell LTE network / Zainul Haslin Abu Hassan - Abu Hassan, Zainul Haslin (2013)
The increase in capacity and system data rate may lead to capacity problems and hence become one of the crucial issues of any Mobile Communication Networks. Although the Long Term Evolution (LTE) is called as 4th Generation of the Mobile Cellular Communication Network, it can no longer solve the problem regarding the capacity of the cell. Deployed femtocells in macrocell are is one of the efficient technologies to improve the performance of mobile services in high traffic congested areas. Femtocells, also known as home base station, are cellular network access points that connect standard mobile devices to a mobile operator's network using residential Digital Subscriber Line (DSL), optical fibres, cable broadband connections or wireless last-mile technologies. It is fully user deployed and can set it by themselves thereby reduce maintenance and operating costs of the operator and at the same time providing better Quality of Service (QoS) to end users. This thesis present the 3rd Generation Partnership Project (3GPP) LTE Power Control mechanism applying to the LTE femtocells for maximising system performance by adapting LTE Fractional Power Control (FPC) scheme on the environment and propose new Open Loop Uplink Power Control (OLUPC) techniques for LTE femtocells environment. A Simulation-based PC program is made to analyse the performance of the LTE femtocell power control schemes. The simulation results indicate the propose scheme is advantageous and can control the transmit power of the UE in femtocell along with the SINR (Signal to Interference plus Noise Ratio) as compared to the conventional open loop power control.